ALGEBRA OF SOCIAL PHENOMENA - Heorhii Slukin; Vitalii Danich (Izdevnieciba "Baltija Publishing", 2023)
The characteristics of modern societies are central to discussions of various types of policy (social, economic, etc.) and are often seen as predictors of socio-economic processes. Any society can be studied through the lens of social phenomena. Hence, it seems fair to assume that the better one understands the nature of social matter and its impact on various processes, the better one's decisions will be able to meet today's challenges. The purpose of this paper is to explain and present the new framework for measuring social phenomena in the form of an algebra based on the definition of social phenomenon, its components, rationality and mathematical logic. Methodology. Using the example of social cohesion, the paper examines the current fundamental methodological approaches to interpreting the definition and, consequently, measuring social phenomena. In this paper, the authors use an analogy with probability space and event algebra to develop their mathematical method. As a result, the article presents and explains the basic terms of the algebra of social phenomena that make up the new concept. Practical implications. The authors' approach to formalisation provides a tool for deriving the measure of a complex phenomenon from the measures of its components (simple phenomena), as demonstrated in the example. Thus, this study enriches the range of methods suitable for deepening one's knowledge of the social characteristics of the society under study. Value/Originality. The concept of algebra as a methodology for measuring social phenomena and establishing dependencies between them on the basis of mathematical logic has not yet been the subject of public discussion. Therefore, this publication is also an invitation to a scientific discussion.